Measuring the social value of prevention and management of type 2 diabetes in a community setting. - clifford, Zoe; Jones, Matthew; Solomon-Moore, Emma; Kok, Michele; Kimberlee, Richard (Advances in Social Sciences Research Journal, 2017)
Background: Type 2 diabetes affects 1 in 20 people over the age of 65. Although there is growing evidence around the effectiveness of lifestyle interventions to prevent or delay the onset of this disease, there is limited evidence of the wider social outcomes and value of such programmes. Social Return on Investment (SROI) is a method of defining, measuring and valuing the wider social outcomes and describing the process of change through the eyes of those who benefit. This paper aims to evaluate the wider impact and social value of the Westbank Living Well, Taking Control (LWTC) community-based diabetes prevention and management education programme. Methods: The SROI methodology involves a mixed methods design. Qualitative methods were used to identify outcomes that were viewed as important by stakeholders in terms of the impact they create. A quantitative approach was used to define the numbers experiencing the outcomes, a monetary representation of the outcomes and their value. Results: SROI analysis found that for every £1 invested in LWTC, there is £5.80 of social return over a three-year period. The sensitivity analysis showed that the value of the social return for every £1 invested in the LWTC is likely to be between £1.30 and £6.57. Conclusions: The study demonstrates the potential social value of a community-based diabetes prevention and management education programme in terms of outcomes for participants, and also the wider outcomes for staff, volunteers, family and friends of the participants and the organisations involved. Better appreciation of such wider outcomes could have an important role in building partnerships, community engagement and political mandate for public health interventions.